Developing priorities and ranking for suitable forest road allocation using Analytical Hierarchy Process (AHP) in Peninsular Malaysia - Norizah, K; Mohd Hasmadi, I (Universiti Kebangsaan Malaysia, 2012)
In hilly forest area, aligning forest roads is the key towards an effective and sustainable forest management. Constraints in forest road planning are mainly due to environmental factors and topographical conditions. Selecting the criteria for planning forest road and setting the priorities, ranking them for environmental sustainability and reduce cost in road construction is important. Different criteria are required at different forest area since the quantifiable relationship between cause and effect to meet the goal are not comprehensively prioritized. In order to solve the problem, the relative importance factor from multi criteria basis, namely Analytic Hierarchy Process (AHP) was applied. Therefore, the objective of this study was to develop priorities and rank a selected criterion for planning forest road in hilly area using AHP approach. Four criteria had been identified to meet the goal of suitable forest road allocation namely slope, river crossing, elevation and existing forest road. The suitable criteria selected were sorted with weight in ranking order to minimize the impact of timber harvesting. Our results showed that the priorities and ranking were as follows; slope (w = 0.558), followed by river crossing (w = 0.303), elevation (w = 0.095) and lastly existing forest road (w = 0.044), respectively. Therefore, the relative preference factor developed in this study can be used by the Forestry Department for formulating suitable forest road allocation in hilly area simultaneously to be integrated with geographic information system technology.